Teenage pregnancy rates and associations with other health risk behaviours: a three-wave cross-sectional study among South African school-going adolescents. Issue 1 (December 2016) - Jonas, Kim; Crutzen, Rik; van den Borne, Bart; Sewpaul, Ronel; Reddy, Priscilla
Abstract Background Teenage pregnancy still remains high in low and middle-income countries (LMIC), as well as in high-income countries (HIC). It is a major contributor to maternal and child morbidity and mortality rates. Furthermore, it has social consequences, such as perpetuating the cycle of poverty including early school dropout by the pregnant adolescent, especially in sub-Saharan Africa (SSA). Few studies in SSA have investigated the trends in teenage pregnancy and the associated factors, while this is critical in fully understanding teenage pregnancy and for promotion of reproductive health among adolescents at large in SSA. Methods To examine the trends in teenage pregnancy and to identify associations with other health risk behaviours in South Africa (SA), a total of 31 816 South African school-going adolescents between 11 to 19 years of age were interviewed in three cross-sectional surveys. Data from the first (2002, n  = 10 549), second (2008, n  = 10 270) and the third (2011, n  = 10 997) nationally representative South African youth risk behaviour surveys (YRBS) were used for this study. Results The overall prevalence of having ever been pregnant among the combined 3-survey sample was self-reported to be 11.0 % and stable across the three surveys. Sexual intercourse among adolescents in SA has decreased from 41.9 % in 2002 to 36.9 % in 2011. However, pregnancy among girls who ever had sex increased from 17.3 % (95 % CI: 0.16–0.19) in 2002, to 23.6 % (95 % CI: 0.21–0.26) in 2008 and decreased to 21.3 % (95 % CI: 0.19–0.23) in 2011. The odds for ever been pregnant were higher for girls who had 2 or more sexual partners (OR: 1.250, 95 % CI: 1.039–1.503), girls who ever used alcohol before sex (OR: 1.373, 95 % CI: 1.004–1.878), practised binge-drinking during the last month (OR: 0.624, 95 % CI: 0.503–0.774), and girls who used mandrax (OR: 1.968, 95 % CI: 1, 243–3.117). The odds for never been pregnant were lower for those who used condoms (OR: 0.462, 95 % CI: 0.309–0.691). Conclusions Girls continue to become pregnant at unacceptably high rates in SA. Sexual intercourse among adolescents in SA has decreased slightly. However, among those who are sexually active pregnancy prevalence rates have increased. More over, this is in the context of high prevalence of HIV and other STI. There is a need to address adolescents' sexual and reproductive health, and several health risk behaviours, including substance use, that are associated with teenage pregnancy in SA.